Premixed Calcium Silicate-Based Root Canal Sealer Reinforced with Bioactive Glass Nanoparticles to Improve Biological Properties - Min-Kyung Jung; So-Chung Park; Yu-Jin Kim; Jong-Tae Park; Jonathan C. Knowles; Jeong-Hui Park; Khandmaa Dashnyam; Soo-Kyung Jun; Hae-Hyoung Lee; Jung-Hwan Lee (MDPI AG, 2022)
Recently, bioactive glass nanoparticles (BGns) have been acknowledged for their ability to promote interactions with the periapical tissue and enhance tissue regeneration by releasing therapeutic ions. However, there have been no studies on calcium silicate sealers with bioactive glass nanoparticle (BGn) additives. In the present study, a premixed calcium silicate root canal sealer reinforced with BGn (pre-mixed-RCS@BGn) was developed and its physicochemical features and biological effects were analyzed. Three specimens were in the trial: 0%, 0.5%, and 1% bioactive glass nanoparticles (BGns) were gradually added to the premixed type of calcium silicate-based sealer (pre-mixed-RCS). To elucidate the surface properties, scanning electron microscopy, X-ray diffraction, and energy-dispersive spectroscopy were used and flowability, setting time, solubility, and radiopacity were analyzed to evaluate the physical properties. Chemical properties were investigated by water contact angle, pH change, and ion release measurements. The antibacterial effects of the bioactive set sealers were tested with Enterococcus faecalis and the viability of human bone marrow-derived mesenchymal stem cells (hMSCs) with this biomaterial was examined. In addition, osteogenic differentiation was highly stimulated, which was confirmed by ALP (Alkaline phosphatase) activity and the ARS (Alizarin red S) staining of hMSCs. The pre-mixed-RCS@BGn satisfied the ISO standards for root canal sealers and maintained antimicrobial activity. Moreover, pre-mixed-RCS@BGn with more BGns turned out to have less cytotoxicity than pre-mixed-RCS without BGns while promoting osteogenic differentiation, mainly due to calcium and silicon ion release. Our results suggest that BGns enhance the biological properties of this calcium silicate-based sealer and that the newly introduced pre-mixed-RCS@BGn has the capability to be applied in dental procedures as a root canal sealer. Further studies focusing more on the biocompatibility of pre-mixed-RCS@BGn should be performed to investigate in vivo systems, including pulp tissue.